CROWDFUNDING AS A MEANS OF LITERACY AND FINANCIAL INCLUSION IN THE COMMUNITY - DESMITA SARI (MANKEU (JURNAL MANAJEMEN KEUANGAN), 2024)
The development of financial technology (fintech) has brought significant changes to the global financial system, including in Indonesia. One of the most rapidly growing innovations is crowdfunding, a public-based funding mechanism conducted through digital platforms. This study aims to explain the role of crowdfunding as a tool to enhance financial literacy and inclusion in the digital era. The research employs a qualitative descriptive literature study approach, utilizing academic references, OJK reports, and case studies of Indonesian crowdfunding platforms such as KitaBisa, GandengTangan, and Bizhare. The results indicate that crowdfunding functions not only as an alternative financing source but also as an educational medium that strengthens public understanding of financial transparency, risk management, and social responsibility. Furthermore, crowdfunding promotes financial inclusion by providing access to capital for underserved groups outside the formal banking system. Therefore, crowdfunding plays a strategic role in fostering an inclusive, transparent, and participatory financial ecosystem.